2021
DOI: 10.3390/pharmaceutics13050709
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence, Challenges, and Opportunities of Physiologically Based Pharmacokinetic Models of Atorvastatin for Decision Making

Abstract: Atorvastatin (ATS) is the gold-standard treatment worldwide for the management of hypercholesterolemia and prevention of cardiovascular diseases associated with dyslipidemia. Physiologically based pharmacokinetic (PBPK) models have been positioned as a valuable tool for the characterization of complex pharmacokinetic (PK) processes and its extrapolation in special sub-groups of the population, leading to regulatory recognition. Several PBPK models of ATS have been published in the recent years, addressing diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 84 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…With few exceptions, the PK studies reported to date consist mainly in classical association studies using noncompartmental PK analysis sometimes performed on healthy volunteers after single dose administration 21,28,32,[35][36][37] or physiologically-based PK models. [40][41][42][43][44] Some population PK (PopPK) studies have been published but with strict, rich sampling and/or in a limited number of (healthy) individuals without considering genetic polymorphisms and, thus, are not likely to reflect the constraints of real-life clinical settings. 29,[45][46][47][48] In this context, with the support of rich datasets from former studies, 49,50 our study aimed at constructing a PopPK model with data prospectively collected in a cohort of ambulatory patients sparsely sampled and including relevant pharmacogenetic information.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
“…With few exceptions, the PK studies reported to date consist mainly in classical association studies using noncompartmental PK analysis sometimes performed on healthy volunteers after single dose administration 21,28,32,[35][36][37] or physiologically-based PK models. [40][41][42][43][44] Some population PK (PopPK) studies have been published but with strict, rich sampling and/or in a limited number of (healthy) individuals without considering genetic polymorphisms and, thus, are not likely to reflect the constraints of real-life clinical settings. 29,[45][46][47][48] In this context, with the support of rich datasets from former studies, 49,50 our study aimed at constructing a PopPK model with data prospectively collected in a cohort of ambulatory patients sparsely sampled and including relevant pharmacogenetic information.…”
Section: How Might This Change Clinical Pharmacology or Translational...mentioning
confidence: 99%
“…9 PK/ PD modeling and simulation are central in informing and personalizing therapy in situations in which gaps in data are expected, such as in rare diseases, [37][38][39] in case of alternative dosing regimens thus repurposing approved drugs. 37,40,41 Thus, the results of the present study may help redefining the current recommendation of a b.i.d. regimen for a selected patient with PV subset (i.e., those with inadequate serum TXB 2 suppression), rather than for the entire PV population.…”
Section: Discussionmentioning
confidence: 62%
“…The in silico modeling of patients with PV with higher TXA 2 production required a comparable increase in the COX‐1 biosynthetic rate as in the ET condition, 9,21 whereas patients with PV with lower platelet TXA 2 production could be modeled by the same parameters of aspirin‐treated non‐PV patients with a presumably normal bone marrow function (Figure 4). 9 PK/PD modeling and simulation are central in informing and personalizing therapy in situations in which gaps in data are expected, such as in rare diseases, 37–39 in case of alternative dosing regimens thus repurposing approved drugs 37,40,41 . Thus, the results of the present study may help redefining the current recommendation of a b.i.d.…”
Section: Discussionmentioning
confidence: 92%
“…Physiologically based pharmacokinetic (PBPK) modeling is a mathematical modeling technique to describe and predict drug disposition in various populations ( Jones and Rowland-Yeo, 2013 ). By integrating population-specific physiologic parameters with drug-specific physicochemical and pharmacokinetics information, PBPK models are increasingly used for the prediction of drug distribution, drug-drug interactions (DDI), transporter evaluation, and extrapolation of drug exposure in age-specific or special subgroups of patients ( Jones et al, 2009 ; Maharaj and Edginton, 2014 ; Reig-Lopez et al, 2021 ). However, the application of PBPK modeling for the active ingredients of herbal medicine was limitedly reported.…”
Section: Introductionmentioning
confidence: 99%